Intrinsic magnetic MXene material as well as preparation method and application thereof
By introducing defects into MXene and using potassium hydroxide-assisted liquid phase self-assembly technology to construct a one-dimensional Archimedes helical structure, the problem of insufficient wave absorption performance of single-component MXene materials is solved, and stable room temperature ferromagnetics and Excellent electromagnetic wave absorption performance.
Patent Information
- Application Number
- CN202411271678.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-11
- Publication Date
- 2025-01-03
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The existing single-component MXene materials lack magnetic loss, impedance mismatch and insufficient attenuation capabilities, resulting in poor electromagnetic wave absorption performance and magnetic particles are prone to agglomeration, which limits the improvement of wave absorption performance.
By introducing defects into MXene, it activates its intrinsic ferromagneticity, enhances magnetic loss, and constructs a one-dimensional Archimedes spiral MXene through potassium hydroxide-assisted liquid phase self-assembly and freeze-drying technology to regulate its magnetism to improve electromagnetic wave absorption performance.
Without introducing magnetic nanoparticles, stable room temperature ferromagneticity and excellent electromagnetic wave absorption ability are achieved, intrinsic electromagnetic parameters are adjusted, and the wave absorption performance of the material is improved.
Smart Images

Figure HDA0005038900620000011 
Figure HDA0005038900620000012 
Figure HDA0005038900620000021
Abstract
Description
Technical Field
[0001] The present invention belongs to the field of preparation of wave-absorbing materials, and specifically relates to an intrinsic magnetic MXene material and a preparation method and application thereof. Background Art
[0002] With the rapid development of radar detection and communication technology, electromagnetic wave technology has provided a lot of convenience for modern life, but it has also brought a series of serious problems such as serious electromagnetic radiation, electromagnetic information leakage and electromagnetic pollution. The development of high-efficiency electromagnetic wave absorbing materials is one of the effective ways to solve the above-mentioned increasingly serious electromagnetic problems.
[0003] MXene materials have attracted widespread attention in the field of electromagnetic wave absorption due to their light weight, excellent chemical stability and significant dielectric loss characteristics. However, the existing single-component MXene materials have poor wave absorption performance due to lack of magnetic loss, impedance mismatch and insufficient attenuation capacity. Using MXene materials as a substrate and compounding with magnetic particles is a common strategy to solve the above problems. However, the design of magnetic particle / MXene composite absorbers is mostly based on semi-empirical rules, lacking precise control of components, interfaces and defects during the reaction process. In addition, due to the limitations of the preparation process, magnetic particles are prone to agglomeration, which further limits the improvement of wave absorption performance. Therefore, regulating the intrinsic magnetism of single-component MXene materials provides a new idea and new way to effectively improve their wave absorption performance. Summary of the invention
[0004] In order to solve the problems of the above-mentioned prior art, the present invention provides an intrinsic magnetic MXene material and its preparation method and application. Under the premise of not introducing magnetic nanoparticles, a single-component pure MXene electromagnetic wave absorption material is designed and developed. By introducing defects into the lattice of MXene, the intrinsic ferromagnetism of MXene is activated, the magnetic loss is enhanced, and impedance matching is achieved. This provides new ideas and strategies for regulating the magnetism of MXene and improving its electromagnetic wave absorption performance.
[0005] The present invention is achieved through the following technical solutions:
[0006] The present invention provides a method for preparing an intrinsic magnetic MXene material, comprising the following steps:
[0007] S1, mixing an aqueous solution of MXene with an alkaline reagent, and dispersing them by ultrasonication to obtain a mixed dispersion; freezing the mixed dispersion into a solid using liquid nitrogen; the alkaline reagent is potassium hydroxide or sodium hydroxide;
[0008] S2, freeze-drying the obtained solid to obtain Archimedean screw-type MXene aerogel;
[0009] S3, heat-treating the Archimedean screw-type MXene aerogel under the protection of an inert gas to obtain an intrinsic magnetic MXene material.
[0010] Preferably, in S1, the mass ratio of MXene to alkaline agent is (70-50):(30-50).
[0011] Preferably, in S1, the MXene is Ti3C2T x .
[0012] Preferably, in S1, the aqueous solution of MXene is prepared by the following method:
[0013] (1) After mixing concentrated HCl and LiF, Ti3AlC2 is added; and the resulting mixture is etched under stirring conditions;
[0014] (2) After the etching is completed, the obtained solution is centrifuged and washed, the supernatant is removed, and the obtained precipitate is collected to obtain a multilayer Ti3C2T x ;
[0015] (3) Stripping stage: Multilayer Ti3C2T x Add into water, ultrasonically disperse, centrifuge, collect the supernatant, and obtain the aqueous solution of MXene.
[0016] Preferably, in S1, the ultrasonic dispersion time is 10 to 30 minutes.
[0017] Preferably, in S2, the freeze-drying conditions are: vacuum degree of 3 to 15 Pa, temperature of -30 to -25°C, and time of 40 to 60 h.
[0018] Preferably, in S3, the heat treatment temperature is 200-700° C. and the time is 1-5 hours.
[0019] The present invention also provides an intrinsic magnetic MXene material obtained by the preparation method as described above, wherein the morphology of the intrinsic magnetic MXene material is a one-dimensional Archimedean spiral structure.
[0020] Preferably, the minimum reflection loss RL of the intrinsic magnetic MXene material is -51.15 to -63.50 dB.
[0021] The present invention also provides the application of the intrinsic magnetic MXene material as an absorbing material in electromagnetic protection.
[0022] Compared with the prior art, the present invention has the following beneficial effects:
[0023] The present invention constructs a one-dimensional Archimedean spiral MXene based on potassium hydroxide-assisted liquid phase self-assembly and freeze-drying technology. The topological deformation of the two-dimensional MXene is affected by van der Waals interactions and elastic barriers, and ice crystal sublimation induces the curling of MXene nanosheets: in the liquid phase self-assembly, the positive charge carried by the potassium metal cations and the negative charge on the surface of the MXene nanosheets produce electrostatic interactions, shielding part of the negative charge on the surface of the MXene nanosheets, reducing the electrostatic repulsion between the MXene nanosheet layers, and promoting the self-assembly of MXene. When the mixed solution is immersed in liquid nitrogen for freezing, the MXene nanosheets are pushed vertically to the bottom under the impact of ice crystals to form a vertically arranged array. After the freeze-drying process, the sublimation of ice crystals induces the deformation of the two-dimensional MXene nanosheets to generate a one-dimensional Archimedean spiral MXene. In the subsequent high-temperature pyrolysis activation process, potassium hydroxide etches the MXene to produce defects. These defects destroy the symmetry of the MXene atomic arrangement, causing unpaired spins to appear in the MXene lattice, and introducing localized magnetic moments, thereby inducing magnetism in the material. Thanks to the unique hierarchical structure of Archimedean spiral MXene, defects in adjacent layers achieve interlayer coupling, which improves magnetism without increasing defect density or losing dielectric properties. In addition, the narrow interlayers of one-dimensional Archimedean spiral MXene can form absorption traps, promoting multiple reflections of electromagnetic waves. Its special three-dimensional porous structure allows electromagnetic waves to be repeatedly scattered and reflected in the structure, extending the transmission path of electromagnetic waves, thereby effectively improving the electromagnetic wave absorption performance of the material. In summary, the present invention prepares ferromagnetic MXene without introducing magnetic nanoparticles, achieves stable room temperature ferromagnetism, enhances the magnetic loss capacity of pure MXene materials, and adjusts its intrinsic electromagnetic parameters. The electromagnetic coupling generated by the derived magnetic resonance optimizes impedance matching, so that the resulting material exhibits excellent electromagnetic wave absorption capacity.
[0024] Furthermore, the present invention can achieve effective regulation of the magnetic properties of MXene materials by controlling the heat treatment temperature.
[0025] The MXene material obtained by the present invention has intrinsic magnetism and exhibits excellent electromagnetic wave absorption ability, which provides a new idea and new approach for effectively improving its wave absorption performance. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0027] Figure 1 The SEM image, room temperature hysteresis loop diagram and three-dimensional reflection loss (RL) diagram of the MXene material prepared in Example 1 of the present invention.
[0028] Figure 2 The SEM image, room temperature hysteresis loop diagram and three-dimensional RL diagram of the MXene material prepared in Example 2 of the present invention.
[0029] Figure 3 This is a three-dimensional RL diagram of the MXene material prepared in Example 3 of the present invention.
[0030] Figure 4 This is a three-dimensional RL diagram of the MXene material prepared in Example 4 of the present invention.
[0031] Figure 5 This is a three-dimensional RL diagram of the MXene material prepared in Example 5 of the present invention.
[0032] Figure 6 This is a three-dimensional RL diagram of the MXene material prepared in Example 6 of the present invention.
[0033] Figure 7 This is a three-dimensional RL diagram of the MXene material prepared in Example 7 of the present invention.
[0034] Figure 8 This is a three-dimensional RL diagram of the MXene material prepared in Example 8 of the present invention.
[0035] Fig. 9 These are the SEM images and three-dimensional RL images of the MXene material prepared in Example 9 of the present invention.
[0036] Fig.10 This is the SEM image of the MXene material prepared in Comparative Example 1 of the present invention.
[0037] Fig.11 These are the SEM images and three-dimensional RL images of the MXene material prepared in Comparative Example 2 of the present invention. DETAILED DESCRIPTION
[0038] The following describes the embodiments of the present invention through specific examples, and those skilled in the art can easily understand other advantages and effects of the present invention from the contents disclosed in this specification. The present invention can also be implemented or applied through other different specific embodiments, and the details in this specification can also be modified or changed in various ways based on different viewpoints and applications without departing from the spirit of the present invention.
[0039] It should be noted that the process equipment or devices not specifically specified in the following embodiments are all conventional equipment or devices in the art.
[0040] It should be noted that the terms "include" and "have" and any variations thereof are intended to cover non-exclusive inclusions. For example, a process, method, system, product or device that includes a series of steps or units is not necessarily limited to those steps or units clearly listed, but may include other steps or units that are not clearly listed or inherent to these processes, methods, products or devices. Moreover, unless otherwise specified, the numbering of each method step is only a convenient tool for identifying each method step, and is not intended to limit the order of arrangement of each method step or to define the scope of the present invention. Changes or adjustments in their relative relationships should also be regarded as the scope of the present invention without substantially changing the technical content.
[0041] The method for preparing the intrinsic magnetic MXene material of the present invention comprises the following steps:
[0042] S1, mixing an aqueous solution of MXene with an alkaline reagent, and dispersing them by ultrasonication to obtain a mixed dispersion; freezing the mixed dispersion into a solid using liquid nitrogen; the alkaline reagent is potassium hydroxide or sodium hydroxide;
[0043] S2, freeze-drying the obtained solid to obtain Archimedean screw-type MXene aerogel;
[0044] S3, heat-treating the Archimedean screw-type MXene aerogel under the protection of an inert gas to obtain an intrinsic magnetic MXene material.
[0045] In the preparation method of the present invention, during the freeze-drying process, the two-dimensional MXene nanosheet undergoes topological deformation and is transformed into a one-dimensional Archimedean screw-type MXene; during the heat treatment process, the alkaline reagent etches the MXene to form defects.
[0046] In some specific embodiments of the present invention, the aqueous solution of MXene is an aqueous solution of a single layer of MXene, which is obtained by the following preparation method:
[0047] (1) After mixing concentrated HCl and LiF, Ti3AlC2 is added; and the resulting mixture is etched under stirring conditions;
[0048] (2) After the etching is completed, the obtained solution is centrifuged and washed, the supernatant is removed, and the obtained precipitate is collected to obtain a multilayer Ti3C2T x ;
[0049] (3) Stripping stage: Multilayer Ti3C2T x Add into water, ultrasonically disperse, centrifuge, collect the supernatant, and obtain the aqueous solution of MXene.
[0050] In some specific embodiments of the present invention, the mass ratio of MXene to alkaline agent is (70-50):(30-50).
[0051] In some specific embodiments of the present invention, the ultrasonic time in S1 is 10 to 30 minutes.
[0052] In some specific embodiments of the present invention, the freeze-drying conditions in S2 are: vacuum degree of 3 to 15 Pa, temperature of -30 to -25°C, and time of 40 to 60 hours.
[0053] In some specific embodiments of the present invention, the heat treatment conditions in S3 are: temperature of 200-700° C., and time of 1-5 hours. By adjusting the temperature of the heat treatment, the magnetic properties of the prepared MXene material can be effectively adjusted.
[0054] Example 1
[0055] The preparation method of the intrinsic magnetic MXene absorbing material of the present invention comprises the following steps:
[0056] (1) Etching stage: In a 100 mL Teflon reactor, 40 mL of concentrated HCl (9 M) and 2 g of LiF were mixed evenly, and then 2 g of Ti3AlC2 was slowly added; the resulting mixture was stirred at 250 rpm at 55°C for 24 hours for etching.
[0057] (2) Centrifugal washing stage: After etching, the obtained solution was centrifuged several times to remove the supernatant and retain the precipitate. Each centrifugation condition was set at 3500 rpm for 5 minutes until the pH value of the solution was close to 6. The obtained precipitate was collected to obtain multilayer Ti3C2T x .
[0058] (3) Stripping stage: Multilayer Ti3C2T x The monolayer Ti3C2T was dispersed in 60 mL of deionized water and then subjected to 60 W ultrasonic treatment in an ice bath for 40 min to promote the separation of MXene flakes. After that, the monolayer was centrifuged at 3500 rpm for 30 min and the supernatant was collected to obtain a monolayer Ti3C2T x MXene slurry.
[0059] (4) Dispersion and freezing: MXene and potassium hydroxide were mixed evenly in a mass ratio of 70%:30% and ultrasonically dispersed for 10 min until a uniform dispersion was formed. Subsequently, liquid nitrogen was used for rapid freezing to freeze the mixed dispersion into a solid for 15 min.
[0060] (5) Freeze-drying process: The frozen solid is placed in a freeze dryer and freeze-dried for 60 hours at a vacuum degree of 3 Pa and a temperature of -25°C to obtain a MXene aerogel with a one-dimensional Archimedean spiral. During this process, the two-dimensional MXene nanosheet undergoes topological deformation and transforms into a one-dimensional Archimedean spiral MXene.
[0061] (6) Heat treatment and activation: The freeze-dried one-dimensional Archimedean spiral MXene aerogel material is taken out and placed in a tubular furnace for heat treatment. Argon is used as the protective gas, and then the temperature is raised programmatically. The calcination temperature is selected to be 200 °C. The freeze-dried Archimedean spiral MXene aerogel material is activated at the set temperature and treated at a constant temperature for 2 h to obtain a defect-rich Archimedean spiral MXene material.
[0062] (7) Electromagnetic properties test: The complex dielectric constant and complex magnetic permeability of the defect-rich Archimedean spiral MXene material were tested by a vector network analyzer. The absorption frequency band studied was 2.0 to 18.0 GHz. The MXene material was mixed with paraffin in a mass ratio of 1:9. The MXene material was immersed in the melted paraffin so that the paraffin could evenly penetrate the MXene sample through capillary action to ensure that the sample structure was not damaged. Finally, the mixture was molded into a coaxial test ring (thickness: 2 mm, inner diameter: 3 mm, outer diameter: 7 mm) for electromagnetic wave absorption performance testing.
[0063] Example 2
[0064] The preparation method of the intrinsic magnetic MXene absorbing material of the present invention comprises the following steps:
[0065] (1) Etching stage: In a 100 mL Teflon reactor, 40 mL of concentrated HCl (9 M) and 2 g of LiF were mixed evenly, and then 2 g of Ti3AlC2 was slowly added; the resulting mixture was stirred at 250 rpm at 55°C for 24 hours for etching.
[0066] (2) Centrifugal washing stage: After etching, the obtained solution was centrifuged several times to remove the supernatant and retain the precipitate. Each centrifugation condition was set at 3500 rpm for 5 minutes until the pH value of the solution was close to 6. The obtained precipitate was collected to obtain multilayer Ti3C2T x .
[0067] (3) Stripping stage: Multilayer Ti3C2T x The monolayer Ti3C2T was dispersed in 60 mL of deionized water and then subjected to 60 W ultrasonic treatment in an ice bath for 40 min to promote the separation of MXene flakes. After that, the monolayer was centrifuged at 3500 rpm for 30 min and the supernatant was collected to obtain a monolayer Ti3C2T x MXene slurry.
[0068] (4) Dispersion and freezing: MXene and potassium hydroxide were mixed evenly in a mass ratio of 70%:30% and ultrasonically dispersed for 10 min until a uniform dispersion was formed. Subsequently, liquid nitrogen was used for rapid freezing to freeze the mixed dispersion into a solid for 15 min.
[0069] (5) Freeze-drying process: The frozen solid is placed in a freeze dryer and freeze-dried for 60 hours at a vacuum degree of 3 Pa and a temperature of -25°C to obtain a MXene aerogel with a one-dimensional Archimedean spiral. During this process, the two-dimensional MXene nanosheet undergoes topological deformation and transforms into a one-dimensional Archimedean spiral MXene.
[0070] (6) Heat treatment and activation: The freeze-dried one-dimensional Archimedean spiral MXene aerogel material was taken out and placed in a tubular furnace for heat treatment. Argon was used as the protective gas, and then the temperature was raised programmatically. The calcination temperature was selected to be 300 °C. The freeze-dried Archimedean spiral MXene aerogel material was activated at the set temperature and treated at a constant temperature for 2 h to obtain a defect-rich Archimedean spiral MXene material.
[0071] (7) Electromagnetic properties test: The complex dielectric constant and complex magnetic permeability of the defect-rich Archimedean spiral MXene material were tested by a vector network analyzer. The absorption frequency band studied was 2.0 to 18.0 GHz. The MXene material was mixed with paraffin in a mass ratio of 1:9. The MXene material was immersed in the melted paraffin so that the paraffin could evenly penetrate the MXene sample through capillary action to ensure that the sample structure was not damaged. Finally, the mixture was molded into a coaxial test ring (thickness: 2 mm, inner diameter: 3 mm, outer diameter: 7 mm) for electromagnetic wave absorption performance testing.
[0072] Example 3
[0073] The preparation method of the intrinsic magnetic MXene absorbing material of the present invention comprises the following steps:
[0074] (1) Etching stage: In a 100 mL Teflon reactor, 40 mL of concentrated HCl (9 M) and 2 g of LiF were mixed evenly, and then 2 g of Ti3AlC2 was slowly added; the resulting mixture was stirred at 250 rpm at 55°C for 24 hours for etching.
[0075] (2) Centrifugal washing stage: After etching, the obtained solution was centrifuged several times to remove the supernatant and retain the precipitate. Each centrifugation condition was set at 3500 rpm for 5 minutes until the pH value of the solution was close to 6. The obtained precipitate was collected to obtain multilayer Ti3C2T x .
[0076] (3) Stripping stage: Multilayer Ti3C2T x The monolayer Ti3C2T was dispersed in 60 mL of deionized water and then subjected to 60 W ultrasonic treatment in an ice bath for 40 min to promote the separation of MXene flakes. After that, the monolayer was centrifuged at 3500 rpm for 30 min and the supernatant was collected to obtain a monolayer Ti3C2T x MXene slurry.
[0077] (4) Dispersion and freezing: MXene and potassium hydroxide were mixed evenly and dispersed by ultrasound in a mass ratio of 70%:30%. The ultrasound time was 10 min until a uniform dispersion was formed. Subsequently, liquid nitrogen was used for rapid freezing to freeze the mixed dispersion into a solid, and the freezing time was 15 min.
[0078] (5) Freeze-drying process: The frozen solid is placed in a freeze dryer and freeze-dried for 60 hours at a vacuum degree of 3 Pa and a temperature of -25°C to obtain a MXene aerogel with a one-dimensional Archimedean spiral. During this process, the two-dimensional MXene nanosheet undergoes topological deformation and transforms into a one-dimensional Archimedean spiral MXene.
[0079] (6) Heat treatment and activation: The freeze-dried one-dimensional Archimedean spiral MXene aerogel material is taken out and placed in a tubular furnace for heat treatment. Argon is used as the protective gas, and then the temperature is raised programmatically. The calcination temperature is selected to be 400 °C. The freeze-dried Archimedean spiral MXene aerogel material is activated at the set temperature and treated at a constant temperature for 2 h to obtain a defect-rich Archimedean spiral MXene material.
[0080] (7) Electromagnetic properties test: The complex dielectric constant and complex magnetic permeability of the defect-rich Archimedean spiral MXene material were tested by a vector network analyzer. The absorption frequency band studied was 2.0 to 18.0 GHz. The MXene material was mixed with paraffin in a mass ratio of 1:9. The MXene material was immersed in the melted paraffin so that the paraffin could evenly penetrate the MXene sample through capillary action to ensure that the sample structure was not damaged. Finally, the mixture was molded into a coaxial test ring (thickness: 2 mm, inner diameter: 3 mm, outer diameter: 7 mm) for electromagnetic wave absorption performance testing.
[0081] Example 4
[0082] The preparation method of the intrinsic magnetic MXene absorbing material of the present invention comprises the following steps:
[0083] (1) Etching stage: In a 100 mL Teflon reactor, 40 mL of concentrated HCl (9 M) and 2 g of LiF were mixed evenly, and then 2 g of Ti3AlC2 was slowly added; the resulting mixture was stirred at 250 rpm at 55°C for 24 hours for etching.
[0084] (2) Centrifugal washing stage: After etching, the obtained solution was centrifuged several times to remove the supernatant and retain the precipitate. Each centrifugation condition was set at 3500 rpm for 5 minutes until the pH value of the solution was close to 6. The obtained precipitate was collected to obtain multilayer Ti3C2T x .
[0085] (3) Stripping stage: Multilayer Ti3C2T x The monolayer Ti3C2T was dispersed in 60 mL of deionized water and then subjected to 60 W ultrasonic treatment in an ice bath for 40 min to promote the separation of MXene flakes. After that, the monolayer was centrifuged at 3500 rpm for 30 min and the supernatant was collected to obtain a monolayer Ti3C2T x MXene slurry.
[0086] (4) Dispersion and freezing: MXene and potassium hydroxide were mixed evenly in a mass ratio of 70%:30% and ultrasonically dispersed for 10 min until a uniform dispersion was formed. Subsequently, liquid nitrogen was used for rapid freezing to freeze the mixed dispersion into a solid for 15 min.
[0087] (5) Freeze-drying process: The frozen solid is placed in a freeze dryer and freeze-dried for 60 hours at a vacuum degree of 3 Pa and a temperature of -25°C to obtain a MXene aerogel with a one-dimensional Archimedean spiral. During this process, the two-dimensional MXene nanosheet undergoes topological deformation and transforms into a one-dimensional Archimedean spiral MXene.
[0088] (6) Heat treatment and activation: The freeze-dried one-dimensional Archimedean spiral MXene aerogel material was taken out and placed in a tubular furnace for heat treatment. Argon was used as the protective gas, and then the temperature was raised programmatically. The calcination temperature was selected to be 700 °C. The freeze-dried Archimedean spiral MXene aerogel material was activated at the set temperature and treated at a constant temperature for 2 h to obtain a defect-rich Archimedean spiral MXene material.
[0089] (7) Electromagnetic properties test: The complex dielectric constant and complex magnetic permeability of the defect-rich Archimedean spiral MXene material were tested by a vector network analyzer. The absorption frequency band studied was 2.0 to 18.0 GHz. The MXene material was mixed with paraffin in a mass ratio of 1:9. The MXene material was immersed in the melted paraffin so that the paraffin could evenly penetrate the MXene sample through capillary action to ensure that the sample structure was not damaged. Finally, the mixture was molded into a coaxial test ring (thickness: 2 mm, inner diameter: 3 mm, outer diameter: 7 mm) for electromagnetic wave absorption performance testing.
[0090] Example 5
[0091] The preparation method of the intrinsic magnetic MXene absorbing material of the present invention comprises the following steps:
[0092] (1) Etching stage: In a 100 mL Teflon reactor, 40 mL of concentrated HCl (9 M) and 2 g of LiF were mixed evenly, and then 2 g of Ti3AlC2 was slowly added; the resulting mixture was stirred at 250 rpm at 55°C for 24 hours for etching.
[0093] (2) Centrifugal washing stage: After etching, the resulting solution is centrifuged several times to remove the supernatant and retain the precipitate. Each centrifugation condition is set at 3500 rpm for 5 minutes until the pH value of the solution reaches
[0094] Close to 6. Collect the resulting precipitate to obtain multilayer Ti3C2T x .
[0095] (3) Stripping stage: Multilayer Ti3C2T x The monolayer Ti3C2T was dispersed in 60 mL of deionized water and then subjected to 60 W ultrasonic treatment in an ice bath for 40 min to promote the separation of MXene flakes. After that, the monolayer was centrifuged at 3500 rpm for 30 min and the supernatant was collected to obtain a monolayer Ti3C2T x MXene slurry.
[0096] (4) Dispersion and freezing: MXene and potassium hydroxide were mixed evenly in a mass ratio of 70%:30% and ultrasonically dispersed for 10 min until a uniform dispersion was formed. Subsequently, liquid nitrogen was used for rapid freezing to freeze the mixed dispersion into a solid for 15 min.
[0097] (5) Freeze-drying process: The frozen solid is placed in a freeze dryer and freeze-dried for 60 hours at a vacuum degree of 3 Pa and a temperature of -25°C to obtain a MXene aerogel with a one-dimensional Archimedean spiral. During this process, the two-dimensional MXene nanosheet undergoes topological deformation and transforms into a one-dimensional Archimedean spiral MXene.
[0098] (6) Heat treatment and activation: The freeze-dried one-dimensional Archimedean spiral MXene aerogel material is taken out and placed in a tubular furnace for heat treatment. Argon is used as the protective gas, and then the temperature is raised programmatically. The calcination temperature is selected to be 300 °C. The freeze-dried Archimedean spiral MXene aerogel material is activated at the set temperature and treated at a constant temperature for 1 h to obtain a defect-rich Archimedean spiral MXene material.
[0099] (7) Electromagnetic properties test: The complex dielectric constant and complex magnetic permeability of the defect-rich Archimedean spiral MXene material were tested by a vector network analyzer. The absorption frequency band studied was 2.0 to 18.0 GHz. The MXene material was mixed with paraffin in a mass ratio of 1:9. The MXene material was immersed in the melted paraffin so that the paraffin could evenly penetrate the MXene sample through capillary action to ensure that the sample structure was not damaged. Finally, the mixture was molded into a coaxial test ring (thickness: 2 mm, inner diameter: 3 mm, outer diameter: 7 mm) for electromagnetic wave absorption performance testing.
[0100] Example 6
[0101] The preparation method of the intrinsic magnetic MXene absorbing material of the present invention comprises the following steps:
[0102] (1) Etching stage: In a 100 mL Teflon reactor, 40 mL of concentrated HCl (9 M) and 2 g of LiF were mixed evenly, and then 2 g of Ti3AlC2 was slowly added; the resulting mixture was stirred at 250 rpm at 55°C for 24 hours for etching.
[0103] (2) Centrifugal washing stage: After etching, the obtained solution was centrifuged several times to remove the supernatant and retain the precipitate. Each centrifugation condition was set at 3500 rpm for 5 minutes until the pH value of the solution was close to 6. The obtained precipitate was collected to obtain multilayer Ti3C2T x .
[0104] (3) Stripping stage: Multilayer Ti3C2T x The monolayer Ti3C2T was dispersed in 60 mL of deionized water and then subjected to 60 W ultrasonic treatment in an ice bath for 40 min to promote the separation of MXene flakes. After that, the monolayer was centrifuged at 3500 rpm for 30 min and the supernatant was collected to obtain a monolayer Ti3C2T x MXene slurry.
[0105] (4) Dispersion and freezing: MXene and potassium hydroxide were mixed evenly in a mass ratio of 70%:30% and ultrasonically dispersed for 10 min until a uniform dispersion was formed. Subsequently, liquid nitrogen was used for rapid freezing to freeze the mixed dispersion into a solid for 15 min.
[0106] (5) Freeze-drying process: The frozen solid is placed in a freeze dryer and freeze-dried for 60 hours at a vacuum degree of 3 Pa and a temperature of -25°C to obtain a MXene aerogel with a one-dimensional Archimedean spiral. During this process, the two-dimensional MXene nanosheet undergoes topological deformation and transforms into a one-dimensional Archimedean spiral MXene.
[0107] (6) Heat treatment and activation: The freeze-dried one-dimensional Archimedean spiral MXene aerogel material was taken out and placed in a tubular furnace for heat treatment. Argon was used as the protective gas, and then the temperature was raised programmatically. The calcination temperature was selected to be 300 °C. The freeze-dried Archimedean spiral MXene aerogel material was activated at the set temperature and treated at a constant temperature for 5 h to obtain a defect-rich Archimedean spiral MXene material.
[0108] (7) Electromagnetic properties test: The complex dielectric constant and complex magnetic permeability of the defect-rich Archimedean spiral MXene material were tested by a vector network analyzer. The absorption frequency band studied was 2.0 to 18.0 GHz. The MXene material was mixed with paraffin in a mass ratio of 1:9. The MXene material was immersed in the melted paraffin so that the paraffin could evenly penetrate the MXene sample through capillary action to ensure that the sample structure was not damaged. Finally, the mixture was molded into a coaxial test ring (thickness: 2 mm, inner diameter: 3 mm, outer diameter: 7 mm) for electromagnetic wave absorption performance testing.
[0109] Example 7
[0110] The preparation method of the intrinsic magnetic MXene absorbing material of the present invention comprises the following steps:
[0111] (1) Etching stage: In a 100 mL Teflon reactor, 40 mL of concentrated HCl (9 M) and 2 g of LiF were mixed evenly, and then 2 g of Ti3AlC2 was slowly added; the resulting mixture was stirred at 250 rpm at 55°C for 24 hours for etching.
[0112] (2) Centrifugal washing stage: After etching, the obtained solution was centrifuged several times to remove the supernatant and retain the precipitate. Each centrifugation condition was set at 3500 rpm for 5 minutes until the pH value of the solution was close to 6. The obtained precipitate was collected to obtain multilayer Ti3C2T x .
[0113] (3) Stripping stage: Multilayer Ti3C2T xThe monolayer Ti3C2T was dispersed in 60 mL of deionized water and then subjected to 60 W ultrasonic treatment in an ice bath for 40 min to promote the separation of MXene flakes. After that, the monolayer was centrifuged at 3500 rpm for 30 min and the supernatant was collected to obtain a monolayer Ti3C2T x MXene slurry.
[0114] (4) Dispersion and freezing: MXene and potassium hydroxide were mixed evenly in a mass ratio of 60%:40% and ultrasonically dispersed for 10 min until a uniform dispersion was formed. Subsequently, liquid nitrogen was used for rapid freezing to freeze the mixed dispersion into a solid for 15 min.
[0115] (5) Freeze-drying process: The frozen solid is placed in a freeze dryer and freeze-dried for 60 hours at a vacuum degree of 3 Pa and a temperature of -25°C to obtain a MXene aerogel with a one-dimensional Archimedean spiral. During this process, the two-dimensional MXene nanosheet undergoes topological deformation and transforms into a one-dimensional Archimedean spiral MXene.
[0116] (6) Heat treatment and activation: The freeze-dried one-dimensional Archimedean spiral MXene aerogel material was taken out and placed in a tubular furnace for heat treatment. Argon was used as the protective gas, and then the temperature was raised programmatically. The calcination temperature was selected to be 300 °C. The freeze-dried Archimedean spiral MXene aerogel material was activated at the set temperature and treated at a constant temperature for 2 h to obtain a defect-rich Archimedean spiral MXene material.
[0117] (7) Electromagnetic properties test: The complex dielectric constant and complex magnetic permeability of the defect-rich Archimedean spiral MXene material were tested by a vector network analyzer. The absorption frequency band studied was 2.0 to 18.0 GHz. The MXene material was mixed with paraffin in a mass ratio of 1:9. The MXene material was immersed in the melted paraffin so that the paraffin could evenly penetrate the MXene sample through capillary action to ensure that the sample structure was not damaged. Finally, the mixture was molded into a coaxial test ring (thickness: 2 mm, inner diameter: 3 mm, outer diameter: 7 mm) for electromagnetic wave absorption performance testing.
[0118] Example 8
[0119] The preparation method of the intrinsic magnetic MXene absorbing material of the present invention comprises the following steps:
[0120] (1) Etching stage: In a 100 mL Teflon reactor, 40 mL of concentrated HCl (9 M) and 2 g of LiF were mixed evenly, and then 2 g of Ti3AlC2 was slowly added; the resulting mixture was stirred at 250 rpm at 55°C for 24 hours for etching.
[0121] (2) Centrifugal washing stage: After etching, the obtained solution was centrifuged several times to remove the supernatant and retain the precipitate. Each centrifugation condition was set at 3500 rpm for 5 minutes until the pH value of the solution was close to 6. The obtained precipitate was collected to obtain multilayer Ti3C2T x .
[0122] (3) Stripping stage: Multilayer Ti3C2T x The monolayer Ti3C2T was dispersed in 60 mL of deionized water and then subjected to 60 W ultrasonic treatment in an ice bath for 40 min to promote the separation of MXene flakes. After that, the monolayer was centrifuged at 3500 rpm for 30 min and the supernatant was collected to obtain a monolayer Ti3C2T x MXene slurry.
[0123] (4) Dispersion and freezing: MXene and potassium hydroxide were mixed evenly at a mass ratio of 50%:50% and ultrasonically dispersed for 10 min until a uniform dispersion was formed. Subsequently, liquid nitrogen was used for rapid freezing to freeze the mixed dispersion into a solid for 15 min.
[0124] (5) Freeze-drying process: The frozen solid is placed in a freeze dryer and freeze-dried for 60 hours at a vacuum degree of 3 Pa and a temperature of -25°C to obtain a MXene aerogel with a one-dimensional Archimedean spiral. During this process, the two-dimensional MXene nanosheet undergoes topological deformation and transforms into a one-dimensional Archimedean spiral MXene.
[0125] (6) Heat treatment and activation: The freeze-dried one-dimensional Archimedean spiral MXene aerogel material was taken out and placed in a tubular furnace for heat treatment. Argon was used as the protective gas, and then the temperature was raised programmatically. The calcination temperature was selected to be 300 °C. The freeze-dried Archimedean spiral MXene aerogel material was activated at the set temperature and treated at a constant temperature for 2 h to obtain a defect-rich Archimedean spiral MXene material.
[0126] (7) Electromagnetic properties test: The complex dielectric constant and complex magnetic permeability of the defect-rich Archimedean spiral MXene material were tested by a vector network analyzer. The absorption frequency band studied was 2.0 to 18.0 GHz. The MXene material was mixed with paraffin in a mass ratio of 1:9. The MXene material was immersed in the melted paraffin so that the paraffin could evenly penetrate the MXene sample through capillary action to ensure that the sample structure was not damaged. Finally, the mixture was molded into a coaxial test ring (thickness: 2 mm, inner diameter: 3 mm, outer diameter: 7 mm) for electromagnetic wave absorption performance testing.
[0127] Example 9
[0128] The preparation method of the intrinsic magnetic MXene absorbing material of the present invention comprises the following steps:
[0129] (1) Etching stage: In a 100 mL Teflon reactor, 40 mL of concentrated HCl (9 M) and 2 g of LiF were mixed evenly, and then 2 g of Ti3AlC2 was slowly added; the resulting mixture was stirred at 250 rpm at 55°C for 24 hours for etching.
[0130] (2) Centrifugal washing stage: After etching, the obtained solution was centrifuged several times to remove the supernatant and retain the precipitate. Each centrifugation condition was set at 3500 rpm for 5 minutes until the pH value of the solution was close to 6. The obtained precipitate was collected to obtain multilayer Ti3C2T x .
[0131] (3) Stripping stage: Multilayer Ti3C2T x The monolayer Ti3C2T was dispersed in 60 mL of deionized water and then subjected to 60 W ultrasonic treatment in an ice bath for 40 min to promote the separation of MXene flakes. After that, the monolayer was centrifuged at 3500 rpm for 30 min and the supernatant was collected to obtain a monolayer Ti3C2T x MXene slurry.
[0132] (4) Dispersion and freezing: MXene and sodium hydroxide were mixed evenly in a mass ratio of 70%:30% and ultrasonically dispersed for 10 min until a uniform dispersion was formed. Subsequently, liquid nitrogen was used for rapid freezing to freeze the mixed dispersion into a solid for 15 min.
[0133] (5) Freeze-drying process: The frozen solid is placed in a freeze dryer and freeze-dried for 60 hours at a vacuum degree of 3 Pa and a temperature of -25°C to obtain a MXene aerogel with a one-dimensional Archimedean spiral. During this process, the two-dimensional MXene nanosheet undergoes topological deformation and transforms into a one-dimensional Archimedean spiral MXene.
[0134] (6) Heat treatment and activation: The freeze-dried one-dimensional Archimedean spiral MXene aerogel material was taken out and placed in a tubular furnace for heat treatment. Argon was used as the protective gas, and then the temperature was raised programmatically. The calcination temperature was selected to be 300 °C. The freeze-dried Archimedean spiral MXene aerogel material was activated at the set temperature and treated at a constant temperature for 2 h to obtain a defect-rich Archimedean spiral MXene material.
[0135] (7) Electromagnetic properties test: The complex dielectric constant and complex magnetic permeability of the defect-rich Archimedean spiral MXene material were tested by a vector network analyzer. The absorption frequency band studied was 2.0 to 18.0 GHz. The MXene material was mixed with paraffin in a mass ratio of 1:9. The MXene material was immersed in the melted paraffin so that the paraffin could evenly penetrate the MXene sample through capillary action to ensure that the sample structure was not damaged. Finally, the mixture was molded into a coaxial test ring (thickness: 2 mm, inner diameter: 3 mm, outer diameter: 7 mm) for electromagnetic wave absorption performance testing.
[0136] Comparative Example 1
[0137] The process is basically the same as Example 1, except that potassium hydroxide is not added in step (4).
[0138] Comparative Example 2
[0139] The method is basically the same as Example 1, except that step (5) is not performed, and the frozen solid is directly subjected to heat treatment and activation.
[0140] Figure 1 This is the SEM image of the MXene material obtained after pyrolysis in Example 1. It can be clearly observed that the MXene sample has a one-dimensional structure ( Figure 1 (b)). The SEM test results show that the two-dimensional morphology of MXene has changed significantly, from two-dimensional nanosheets to one-dimensional structures, and the defective Archimedean screw-shaped MXene material has been successfully prepared.
[0141] The magnetic properties of the material in Example 1 were further characterized by measuring the MH curve of the magnetization intensity of the MXene material obtained in Example 1 as a function of the applied magnetic field at room temperature using a comprehensive physical property measurement system (PPMS). Figure 1 As can be seen in (c), the magnetization intensity of the MXene material obtained in Example 1 shows a nonlinear response to the applied magnetic field, and its saturation magnetization intensity reaches 1.08emu g –1 , indicating that the defective Archimedean screw MXene material has room temperature ferromagnetic properties.
[0142] The defective Archimedean spiral MXene material obtained in Example 1 was mixed with paraffin at a mass ratio of 1:9 to form a coaxial ring sample with an inner and outer diameter of 3 mm and 7 mm, respectively, for electromagnetic parameter testing. According to the obtained electromagnetic parameters, the reflection loss RL of the material is calculated using the transmission line method in dB. When the RL of the material is less than -10dB, it indicates that the absorbing material can absorb more than 90% of electromagnetic waves. When the RL is less than -20dB, it indicates that the absorbing material has an absorbing performance equivalent to absorbing more than 99% of electromagnetic waves. The smaller the RL, the better the absorbing performance. Figure 1 (d) is a three-dimensional reflection loss diagram of the defective one-dimensional Archimedean spiral MXene material in the frequency range of 2.0 to 18.0 GHz in Example 1. According to the calculation results, the minimum reflection loss RL can reach -52.69 dB, which further proves that the prepared defective Archimedean spiral MXene material has excellent electromagnetic wave absorption performance.
[0143] The electromagnetic parameter test of the Archimedean screw-type MXene material prepared in Examples 2 to 4 was performed in the same manner as above. According to the electromagnetic parameter test results ( Figures 2 to 4 ), the minimum reflection losses of the MXene materials of Examples 2 and 4 are -55.13 and -51.15 dB respectively, and the minimum reflection loss of the Archimedean screw-type MXene material with defects in Example 3 can reach -63.45 dB, showing excellent electromagnetic wave absorption performance. By comparing Examples 1 to 4, it can be seen that the present invention can effectively control the magnetic size of the MXene material by controlling the heat treatment temperature.
[0144] Example 5 and Example 6 are basically the same as Example 1, except that the time is 1 h and 5 h respectively. Example 7 and Example 8 are basically the same as Example 1, except that the mass ratio is 60%:40% and 50%:50% respectively. Example 9 is basically the same as Example 1, except that potassium hydroxide is replaced with sodium hydroxide in step (4).
[0145] The electromagnetic parameter test of the Archimedean screw-type MXene materials prepared in Examples 5 to 9 was carried out in the same manner as above. According to the electromagnetic parameter test results ( Figures 5 to 9 ), it was found that the minimum reflection loss of the defective Archimedean spiral MXene materials in Examples 5 and 6 can reach -51.17 and -56.15 dB, respectively, and the minimum reflection loss of the defective Archimedean spiral MXene materials in Examples 7 and 8 can reach -52.10 and -59.95 dB, respectively, showing excellent electromagnetic wave absorption performance. The minimum reflection loss of the defective Archimedean spiral MXene material in Example 9 can reach -53.90 dB. By comparing Examples 5 to 9, it can be seen that the present invention can effectively control the wave absorption performance of the MXene material by controlling the heat treatment time and the mass ratio of the raw materials.
[0146] The above research results of the present invention show that the defective Archimedean spiral MXene material designed by the present invention realizes the interlayer coupling of defective MXene by introducing local magnetic moments and combining its unique curled hierarchical structure. Without adding magnetic nanoparticles, the material exhibits the characteristics of ferromagnetic MXene and successfully activates the magnetic loss capacity of pure MXene materials. Compared with traditional magnetic particle-MXene composite absorbers, this new defective MXene material does not require the addition of magnetic nanomaterials. By regulating the inherent defects of MXene, magnetic losses are introduced into dielectric loss-type MXene materials, thereby optimizing electromagnetic parameters and achieving impedance matching. In addition, under a certain range of heat treatment temperature, heat treatment time and mass ratio of raw materials, the defect-rich Archimedean spiral MXene material can still maintain stable electromagnetic wave absorption performance.
[0147] Fig.10 This is a SEM image of the product prepared in Comparative Example 1. As shown in the SEM image, MXene exhibits a typical two-dimensional sheet cross-linked network structure, and there is no three-dimensional oriented arrangement structure assembled by one-dimensional MXene nanoscrolls. The experimental results of Comparative Example 1 show that when the system does not contain potassium metal cations, the self-assembly of two-dimensional MXene nanosheets cannot be effectively promoted. This is because the metal cations are not adsorbed on the MXene surface, resulting in the ineffective neutralization of its negative charge. Therefore, potassium hydroxide is one of the key factors in inducing the formation of a one-dimensional structure in two-dimensional MXene nanosheets.
[0148] Fig.11 This is the SEM image of the product prepared in Comparative Example 2. As shown in the SEM image, the structure of MXene collapses and does not show typical one-dimensional structural characteristics. This proves that in the freeze-drying stage of the embodiment of the present invention, as the ice sublimates layer by layer, the vertically arranged MXene nanosheets begin to gradually expose and lose the support of ice crystals, thereby causing the curling of the two-dimensional MXene nanosheets to form a one-dimensional structure. After further freeze-drying, MXene aerogel is formed. The MXene nanosheets without a one-dimensional structure in Comparative Example 2 were further tested for their wave absorption performance. Fig.11 The middle figure (b) shows that its minimum reflection loss is only -3.90dB, which further verifies the structural and functional advantages of the one-dimensional MXene with unique Archimedean screw characteristics.
Claims
1. A method for preparing an intrinsic magnetic MXene material, characterized in that: The following steps are involved: S1, mixing an aqueous solution of MXene with an alkaline reagent, and dispersing them by ultrasonication to obtain a mixed dispersion; freezing the mixed dispersion into a solid using liquid nitrogen; the alkaline reagent is potassium hydroxide or sodium hydroxide; S2, freeze-drying the obtained solid to obtain Archimedean screw-type MXene aerogel; S3, heat-treating the Archimedean screw-type MXene aerogel under the protection of an inert gas to obtain an intrinsic magnetic MXene material.
2. The method for preparing the intrinsic magnetic MXene material according to claim 1, characterized in that: In S1, the mass ratio of MXene to alkaline reagent is (70-50):(30-50).
3. The method for preparing the intrinsic magnetic MXene material according to claim 1, characterized in that: In S1, the MXene is Ti3C2T x .
4. The method for preparing the intrinsic magnetic MXene material according to claim 1, characterized in that: In S1, the aqueous solution of MXene is prepared by the following method: (1) After mixing concentrated HCl and LiF, Ti3AlC2 is added; and the resulting mixture is etched under stirring conditions; (2) After the etching is completed, the obtained solution is centrifuged and washed, the supernatant is removed, and the obtained precipitate is collected to obtain a multilayer Ti3C2T x ; (3) Stripping stage: Multilayer Ti3C2T x Add into water, ultrasonically disperse, centrifuge, collect the supernatant, and obtain the aqueous solution of MXene.
5. The method for preparing the intrinsic magnetic MXene material according to claim 1, characterized in that: In S1, the ultrasonic dispersion time is 10 to 30 minutes.
6. The method for preparing the intrinsic magnetic MXene material according to claim 1, characterized in that: In S2, the freeze-drying conditions are: vacuum degree of 3 to 15 Pa, temperature of -30 to -25°C, and time of 40 to 60 h.
7. The method for preparing the intrinsic magnetic MXene material according to claim 1, characterized in that: In S3, the heat treatment temperature is 200-700°C and the time is 1-5 hours.
8. The intrinsic magnetic MXene material obtained by the preparation method according to any one of claims 1 to 7, characterized in that: The morphology of the intrinsic magnetic MXene material is a one-dimensional Archimedean spiral structure.
9. The intrinsic magnetic MXene material according to claim 8, characterized in that The minimum reflection loss RL of the intrinsic magnetic MXene material is -51.15 to -63.50 dB.
10. Application of the intrinsic magnetic MXene material according to claim 8 as an absorbing material in electromagnetic protection.
Citation Information
Cited By
Preparation method of three-dimensional porous Ti3C2Tx MXene
CN120172409A
Bimetal MXene TiVCTx / Fe3O4 composite material as well as preparation method and application thereof
CN120757152A